Transformative deep learning in secondary education: the 3P framework for inclusive and sustainable knowledge development - Efendi Hidayatullah (Priviet Social Sciences Journal, 2025)
This study explores the potential of the 3P (Precise, Process, Product) framework to incorporate the principles of transformative and deep learning in secondary education. This research addresses the urgent need for meaningful, reflective, and student-centered learning to tackle the complex challenges of the 21st century. A qualitative case study was conducted at a secondary school using purposive sampling of curriculum coordinators, teachers, and policymakers. Data were gathered through semi-structured interviews, focus group discussions, and observation of classes. Thematic analysis, supported by NVivo 12 software, showed that the Precise component helps formulate clear and focused learning objectives; the Process component encourages reflective dialogue, active participation, and an inclusive learning environment; and the Product component fosters authentic, project-based assessment practices. The findings indicate that the 3P framework has shifted learning from exam-centered methods to an emphasis on deep understanding, inclusivity, and global citizenship. Challenges included gaps in teacher training, low digital literacy, and unequal access, while solutions emerged at the teacher, school, and policy levels. The framework proved to be versatile and effective, enhancing students’ learning identity and social awareness, and aligning curriculum standards with classroom practice. This study offers a conceptual contribution to curriculum transformation by presenting an adaptive and sustainable pedagogical model that supports Sustainable Development Goal (SDG) 4 on inclusive and quality education.